2010
DOI: 10.3346/jkms.2010.25.7.1034
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Extensive Upper Abdominal Surgery in Elderly Patients with Advanced Epithelial Ovarian Cancer

Abstract: We performed a retrospective study to evaluate the feasibility and safety of extensive upper abdominal surgery (EUAS) in elderly (≥65 yr) patients with advanced ovarian cancer. Records of patients with advanced epithelial ovarian cancer who received surgery at our institution between January 2001 and June 2005 were reviewed. A total of 137 patients including 32 (20.9%) elderly patients were identified. Co-morbidities were present in 37.5% of the elderly patients. Optimal cytoreduction was feasible in 87.5% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Therefore radical surgery is thought to be applied to gastric cancer in elderly patients without significant risk of complications. This finding is similar to the result of a previous study about ovarian cancer, which revealed that extensive upper abdominal surgery is feasible in elderly patients ( 9 ). However considering that elderly patients have more risk of disease-related complications and larger rate of comorbidities, the decision for whether to do surgery for those with serious comorbidities should be considerate.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore radical surgery is thought to be applied to gastric cancer in elderly patients without significant risk of complications. This finding is similar to the result of a previous study about ovarian cancer, which revealed that extensive upper abdominal surgery is feasible in elderly patients ( 9 ). However considering that elderly patients have more risk of disease-related complications and larger rate of comorbidities, the decision for whether to do surgery for those with serious comorbidities should be considerate.…”
Section: Discussionsupporting
confidence: 91%
“…This study found that the elderly group did not receive benefit from the interval cytoreduction with HIPEC treatment and instead experienced postoperative morbidity, with the most common being grade 4 hemoperitoneum and grade 3 intra-abdominal fluid collection in 22.2% of women ( 17 ). Another study that evaluated the feasibility and safety of extensive upper abdominal surgery (EUAS) in elderly patients with advanced ovarian cancer found no significant difference to that of younger patients, and concluded that EUAS procedures are feasible in this elderly population ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…32,37,46Y49 Regarding postoperative morbidity, study results were inconsistent. 35,37 Elderly patients with ovarian cancer were less often treated by optimal surgery, and this was associated with decreased survival in large population-based studies. 34,36,38,43 However, age was also a significant survival factor after adjusting for other significant survival factors.…”
Section: Elderly Patients With Ovarian Cancermentioning
confidence: 99%